Climate Variability and International Migration: The Importance of the Agricultural Linkage - Ruohong Cai; Shuaizhang Feng; Mariola Pytliková; Michael Oppenheimer (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
While there is considerable interest in understanding the climate-migration relationship, particularly in the context of concerns about global climatic change, little is known about underlying mechanisms. We analyze a unique and extensive set of panel data characterizing annual bilateral international migration flows from 163 origin countries to 42 OECD destination countries covering the last three decades. We find a positive and statistically significant relationship between temperature and international outmigration only in the most agriculture-dependent countries, consistent with the widely-documented adverse impact of temperature on agricultural productivity. In addition, migration flows to current major destinations are especially temperature-sensitive. Policies to address issues related to climate-induced international migration would be more effective if focused on the agriculture-dependent countries and especially people in those countries whose livelihoods depend on agriculture.
Keywords: 330; International migration; Climate variability; Agricultural productivity